Peran Jumatul Khaira dalam Pelestarian Budaya Tenun di Balai Cacang Tahun 1975–2024 - Restu Wahyuni; Dedi Arsa (Lembaga Yasin AlSys, 2026)
Traditional Minangkabau weaving has been widely studied from symbolic and historical perspectives, yet research highlighting the role of individual artisans as key agents of cultural preservation at the community level remains limited. This study aims to analyze the role of Jumatul Khaira in preserving weaving culture in Balai Cacang over the period 1975–2024. It employs a qualitative approach with a historical research method and a descriptive-historical design, involving purposively selected participants including the principal artisan, customary leaders, family members, and local community members. Data were collected through in-depth interviews, field observations, literature review, and documentation, and were analyzed using source criticism and interpretive synthesis. The findings show that cultural preservation has been carried out through hands-on weaving practice, the use of digital media as a means of cultural exposure, and social and customary collaboration; however, the regeneration of weavers has not proceeded effectively due to economic factors, social perceptions, and limited ongoing training. These findings underscore the importance of individual actors in sustaining intangible cultural heritage and provide practical implications for the formulation of preservation strategies based on community empowerment and the strengthening of the creative economy at the local level.